Optimizing the Relaxivity of MRI Probes at High Magnetic Field Strengths With Binuclear GdIII Complexes - Leone, Loredana; Ferrauto, Giuseppe; Cossi, Maurizio; Botta, Mauro; Tei, Lorenzo (Frontiers in Chemistry, 2018)
The key criteria to optimize the relaxivity of a Gd(III) contrast agent at high fields (defined as the region ≥ 1.5 T) can be summarized as follows: i) the occurrence of a rotational correlation time R in the range of ca. 0.2 - 0.5 ns; ii) the rate of water exchange is not critical, but a tauM < 100 ns is preferred; iii) a relevant contribution from water molecules in the second sphere of hydration. In addition, the use of macrocycle-based systems ensures the formation of thermodynamically and kinetically stable Gd(III) complexes. Binuclear Gd(III) complexes could potentially meet these requirements. Their efficiency depends primarily on the degree of flexibility of the linker connecting the two monomeric units, the absence of local motions and the presence of contribution from the second sphere water molecules. With the aim to maximize relaxivity (per Gd) over a wide range of magnetic field strengths, two binuclear Gd(III) chelates derived from the well-known macrocyclic systems DOTA-monopropionamide and HPDO3A (Gd2L1 and Gd2L2, respectively) were synthesized through a multistep synthesis. Chemical Exchange Saturation Transfer (CEST) experiments carried out on Eu2L2 at different pH showed the occurrence of a CEST effect at acidic pH that disappear at neutral pH, associated with the deprotonation of the hydroxyl groups. Then, a complete 1H and 17O NMR relaxometric study was carried out in order to evaluate the parameters that govern the relaxivity associated with these complexes. The relaxivities of Gd2L1 and Gd2L2 (20 MHz, 298 K) are 8.7 and 9.5 mM-1 s-1, respectively, 77% and + 106% higher than the relaxivity values of the corresponding mononuclear GdDOTAMAP-En and GdHPDO3A complexes. A significant contribution of second sphere water molecules was accounted for the strong relaxivity enhancement of Gd2L2. MR phantom images of the dinuclear complexes compared to GdHPDO3A, recorded at 7 T, confirmed the superiority of Gd2L2. Finally, ab initio (DFT) calculations were performed to obtain information about the solution structure of the dinuclear complexes.